Co-simulation-based conventional exergy evaluation of a hybrid energy generation-vanadium redox flow battery-air source heat pump system - Yesilyurt, Muhammed Samil; Ozcan, Huseyin Gunhan; Yavasoglu, Huseyin Ayhan (PERGAMON-ELSEVIER SCIENCE LTD, 2023)
A conventional exergy assessment approach permits determining the magnitudes of irreversibility that have happened within the investigated system components, which indicates the potential for improvement for these components. In this study, this approach was applied to a hybrid powered air source heat pump with vanadium redox flow battery system through co-simulated (solar photovoltaic and wind turbine) TRNSYS integrated with MATLAB Simulink) work. Due to the absence of a sophisticated VRFB model in the TRNSYS application, the battery model created in the Matlab Simulink environment was utilized and then summoned into the TRNSYS simulation studio by use of the TRNSYS utility model.Exergy destruction and exergy efficiency were used as performance criteria for evaluating the conventional exergy performance of the utilized components in the established co-simulation model. While yearly cumulative exergy destruction values ranged from 194.2 kWh for R to 23318.2 kWh for the PV field, annual average exergy efficiency amounts varied between 0.0494 for ASHP and 0.9345 for R. The PV field with the highest exergy destruction and relatively low exergy efficiency causing the highest improvement priority, but the opposite is true for power conditioning equipment, specifically IR and R.
Keywords: Exergy; Co-simulation; Solar PV; Wind turbine; Vanadium redox flow battery; Numerical study; EQUIVALENT-CIRCUIT MODEL; WIND; POWER; PERFORMANCE; PV; VIABILITY; Thermodynamics; Energy & Fuels